A third-order Nakashima pseudo-Runge-Kutta method - Lim, Tian Hwee (Sunway University, 2014)
In this paper, we present a third order Nakashima pseudo-Runge-Kutta method. This method is derived by minimizing the error bound to determine the free parameters. Since the proposed method is only two-stages, it is cheaper than the traditional method. The stability of the method is analyzed and the numerical results are tabulated to compare with the traditional method.